Level of knowledge on prenatal's factors of risk to prevention of disabilities and personal development in teen pregnant in the cono sur of Lima- 2007 - Masías Ynocencio, Ysabel (2009)
This study is framed within educational psychology, focusing on the promotion and prevention of integral health of adolescents and on the efforts to reduce the risk of disability in the baby to be born, same that can originate as a result of ignorance and lack of information from the side of the expectant, future mother regarding biological and environmental biological risks factors. Motivated by these questions, we asked ourselves ¿What is the relationship existing between the level of knowledge of prenatal risk factors for the prevention of disabilities and personal development of adolescent, pregnant mothers in the Southern Section of Lima? This is a study of the descriptive type and of correlation design performed on a sample of 328 pregnant adolescents between 13 and 19 years of age in the Southern Section of Lima. The results show the existence of a statistically significant, positive and of tall degree correlation between the total risk factors and dangers of prenatal disability and total risk factors personal development. Significant statistical differences were also found between all levels of knowledge of risk factors and dangers of prenatal disability according to age. And lastly, pregnant adolescents present a profile of moderate personal development and a low short level of general knowledge regarding the risks factors and dangers of prenatal disability